Association of JAZF1 and TSPAN8/LGR5 variants in relation to type 2 diabetes mellitus in a Saudi population. Issue 1 (December 2015) - Alharbi, Khalid; Ali Khan, Imran; Syed, Rabbani; Alharbi, Fawiziah; Mohammed, Abdul; Vinodson, Benjamin; Al-Daghri, Nasser
Abstract Background Type 2 diabetes mellitus (T2DM) is a chronic and multifactorial disease with a rapidly rising incidence in Saudi Arabia. Various genes including zinc finger protein 1 (JAZF1 ) and tetraspanin 8/leucine-rich repeat-containing G protein-coupled receptor (TSPAN8/LGR5 ) have been previously described to be associated with T2DM. This study investigated the association ofJAZF1 (rs864745) andTSPAN8 (rs7961581) with T2DM in a Saudi population. Methods Genomic DNA samples from 400 Saudi T2DM patients and 400 healthy controls were genotyped and analyzed using a polymerase chain reaction-restriction fragment length polymorphism method. The difference between the genotype frequencies were carried out with Chi-square test. Odds ratio, 95 % confidence intervals and p values were calculated using multinomial logistic regression. Dominant and recessive models were implemented to show the statistical significances. Analysis of variance was used to compare differences between genotypes for the various parameters. Results Distribution frequencies of the AA, AG, and GG genotypes ofJAZF1 (rs864745) differed significantly among T2DM patients and healthy controls (p  < 0.05). The AG and GG genotypes were independently and significantly associated with a T2DM risk after adjusting for factors such as age, sex, and body mass index [odds ratio (OR) 2.1 (95 % confidence interval (CI) 1.3–3.4);p  = 0.002] and [OR 1.9 (95 % CI 1.2–3.1);p  = 0.005], respectively. A genotype-based stratification of anthropometric and biochemical data revealed that the AG + GG genotype is associated with waist circumference (p  = 0.04) and fasting blood glucose (p  = 0.01) and high-density lipoprotein cholesterol levels (p  = 0.02). None of the allele or genotype showed the significant association between the T2DM cases and control subjects in rs7961581 polymorphism in TSPAN8/LGR5 gene. Conclusion The rs864745 variant inJAZF1 gene may act as genetic risk factors for the development of T2DM in a Saudi population.